Theoretical and Practical Issues in Business Valuation (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
Business valuation is dealing with a series of difficulties, legislative and/or normative inaccuracies, as well as problems related to divergent results obtained by standard approaches. This material is synthesizing some of these problems, highlighting possible research directions. Each of the standard approaches is investigated, theoretically and practically analyzed, and the conclusions constitute a basis for developing new theories in the field of valuation.